(untitled) (Eurasian Journal of Ecology, 2016)
Long term coexistence of many indigenous and non-commercial alien fishes was shown as result of experiments in aquariums. Stone moroco (topmouth gudgeon) Pseudorasbora parva has the largest adaptive possibilities. Unfavorable impact of stone moroco to the other fish species was observed.